2014
DOI: 10.1038/sc.2014.70
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study for the assessment of physical activity using a triaxial accelerometer with a gyro sensor on the upper limbs of subjects with paraplegia driving a wheelchair on a treadmill

Abstract: Objective: This study aimed to examine whether, on the basis of the relationship between sensors attached on the upper limbs and energy expenditure (EE) at the time of wheelchair propulsion, there are differences in the measurement of EE depending on the sensor attachment site and whether addition of the angular velocity information to the acceleration value is advantageous. We also aimed to clarify the variables used to estimate EE as well as the estimated error. Setting: Laboratory of the National Hospital O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The mean difference represents the estimated bias, while the 95 percent limits of agreement provide an idea of how far apart two measures are likely to be for most individuals. Three studies constructed the Bland-Altman plots and reported the mean difference and the 95 percent limits of agreement (Tables 1-3) [29,35,50]. The ICC, on the other hand, is a reliability measure that considers the systematic differences in paired observations [54].…”
Section: Wheelchair Movementsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean difference represents the estimated bias, while the 95 percent limits of agreement provide an idea of how far apart two measures are likely to be for most individuals. Three studies constructed the Bland-Altman plots and reported the mean difference and the 95 percent limits of agreement (Tables 1-3) [29,35,50]. The ICC, on the other hand, is a reliability measure that considers the systematic differences in paired observations [54].…”
Section: Wheelchair Movementsmentioning
confidence: 99%
“…Two studies used doubly labeled water [24,35], and 14 studies used metabolic analysis systems such as Cosmed K4b2 or Quark b2 (COSMED; Rome, Italy), TrueOne 2400 computerized metabolic system (TrueOne; Salt Lake City, Utah), Oxycon mobile (Viasys Healthcare; Hochberg, Germany), gas analyzer (AR-1 type-4, Arco System; Chiba, Japan), and Metabolic Analysis System (Aerosport Inc; Ann Arbor, Michigan) as the criterion for measuring energy cost [27][28][29][30][31][32][33][34][37][38][39][40]42,50]. Other methods, including video analysis, observation, direct measurements, and motion capture systems, were used as reference comparisons for validating wheelchair and user movements [34,36,41,[43][44][45][46]49,[51][52].…”
Section: Outcome Measures Gold Standards and Reference Comparisonsmentioning
confidence: 99%
See 3 more Smart Citations